EFEKTIFITAS COMSUMPTION METER SEBAGAI MEDIA KONTROLBAHAN BAKAR DAN PENDETEKSI KONDISI KENDARAAN RODA EMPAT - Barry Nur Setyanto, Agus Irawan, Muhammad Hidayat (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research is aimed at finding the effectiveness of consumption meter whichcan monitor the fuel consumption of four wheeled vehicles, and also finding therelationship between the driving behavior with fuel consumption as well as finding therelationship between the wasteful fuel consumption and the car condition. Consumptionmeter is a means of monitoring the fuel consumption that drivers can use as one of themedia to help them drive the cars with economical fuel consumption.This research started with producing an instrument in the form of consumptionmeter and then accuracy test, precision test, range and response of consumption meterwas initiated by doing the measurement and collection of data to programmicrocontroller ATMEGA8535. The next step is the effectiveness test conducted step bystep. After this the data were collected. The data are in the form of the amount of fuelconsumed by the car driven the driver who did not look at the tool while driving and theone consumed by the car driven by the driver who looked at the tool while driving. Thedata also include the amount of fuel consumption before and after tune up was done.After the data were complete, a statistic test was applied.The result of testing Consumption Meter indicates that this tool shows a high levelof effectiveness. In other words, it can be effectively used to control the fuelconsumption. Furthermore, the behaviour of the drivers is closely related to the fuelconsumption in that the better the driving is, the more economical the fuel consumptionis. In addition, there is a close relationship between the wastefulness of the fuelconsumption and the early detection of the four wheeled vehicles’ condition. It can besaid that the fuel consumption reflects the condition of the vehicles because the worsethe condition of the vehicle is, the more wasteful the fuel consumption is.Keyword: Effectiveness, consumption meter, fuel consumption control, car, condition